KELEMBAGAAN MITIGASI KEKERINGAN DI KABUPATEN GROBOGAN (Institution of drought mitigation in Grobogan Regency) - Faiqotul Falah; Purwanto Purwanto (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2018)
ABSTRACTDrought that occurs almost every year in Grobogan Regency should be anticipated and mitigated by all stakeholders. This paper aims to review the institutional aspects on drought mitigation in Grobogan, as a source to develop a policy on drought mitigation. The data were collected through literature review, structured interviews, and focus group discussion. The data analysis was conducted qualitatively using analysis matrixes of policies’ content, stakeholders’ roles, and institutional capabilities. This study showed that : 1) The government of Grobogan Regency had issued six regulations related to general disaster mitigation and strategy of drinking water supply, but no spesific regulation on drought mitigation issued yet; 2) there is no database on the losses caused by drought and no information about potential water source locations in Grobogan Regency; 3) there are no master plans to anticipate and mitigate drought disasters; and 4) a Disaster Response Forum and Drinking Water & Environmental Health Working Group have been established, but not specifically dealing with drought. The required steps to mitigate drought in Grobogan are: 1) Establishment of Drought Mitigation Forum; 2) Preparation of drought information database including identification of new water sources and water conservation technology; 3) Preparation of Drought Mitigation Master plan; and 4) Drafting and establishing local regulations on water utilization, protection and utilization of springs, and drought mitigation system.Keywords: drought; institution; mitigation; master plan ABSTRAKKekeringan yang terjadi hampir setiap tahun di Grobogan seharusnya dapat diantisipasi dan dikurangi dampak negatifnya secara bersama oleh semua pihak yang terkait. Tulisan ini bertujuan mengkaji kelembagaan mitigasi kekeringan di Kabupaten Grobogan, sebagai bahan penyusunan kebijakan mitigasi kekeringan. Pengumpulan data dilakukan dengan metode studi pustaka, wawancara terstruktur, dan diskusi kelompok terarah. Analisis data dilakukan secara kualitatif dengan bantuan matrik analisis isi kebijakan, matrik peran parapihak, serta matrik analisis kapabilitas lembaga. Hasil kajian menunjukkan bahwa : 1) Pemerintah Kabupaten Grobogan telah mengeluarkan enam peraturan terkait penanggulangan bencana secara umum serta strategi penyediaan air minum, namun belum ada aturan khusus mengenai mitigasi kekeringan; 2) belum ada data kerugian akibat kekeringan yang terjadi setiap tahun, serta data titik-titik potensi sumber air di Kabupaten Grobogan; 3) belum ada rencana induk untuk antisipasi dan mitigasi bencana kekeringan, dan 4) telah dibentuk Forum Tanggap Bencana dan Pokja AMPL (Air Minum Penyehatan Lingkungan), namun tidak secara khusus menangani kekeringan. Langkah-langkah yang perlu dilakukan untuk mitigasi kekeringan di Kabupaten Grobogan adalah : 1) Pembentukan Forum Mitigasi Kekeringan; 2) Penyusunan database informasi bencana kekeringan, termasuk identifikasi sumber air dan teknologi konservasi air yang aplikatif; 3) Penyusunan Rencana Induk Mitigasi Kekeringan; dan 4) Penyusunan dan penetapan aturan pemanfaatan air, aturan perlindungan dan pemanfaatan mata air, serta sistem mitigasi kekeringan.Kata kunci: kekeringan; kelembagaan; mitigasi; rencana induk